Исследование дифракции плоской Е-поляризованной волны на металлических решетках - Буданов, В.Е.; Масалов, С.А.; Шестопалов, В.П. (Radiotekhnika)
Исследование дифракции плоской Е-поляризованной волны на металлических решетках